Effect of various enhancers on diclofenac sodium flux through human placental membrane, human amnion membrane and newborn pig skin - Jaratluck Akanimanee (Chulalongkorn University, 2014)
Thesis (M.Sc. in Pharm)--Chulalongkorn University, 1995